Who's in the driver's seat? Impact on social participation and psychosocial wellbeing in adults aged 50 and over - Mc Garrigle, Christine; Kenny, Rose (My University, 2019)
Social participation is important to maintain physical and mental wellbeing in older age. We examined how transport mode and current driving status affects social participation and psychosocial wellbeing. Data were collected from 8092 community-dwelling adults aged ≥50 years in The Irish Longitudinal Study on Ageing (TILDA), a nationally representative cohort study. Regression analysis was used, examining associations between transport mode and driving status with depressive symptoms, quality of life, loneliness, monthly involvement in active social leisure activities and volunteering and social network strength. 89.8% of adults travel most frequently by car; 72.2% drive themselves. Driving, being driven by a spouse/partner and taking public transport were independently associated with better indicators of social participation and psychosocial wellbeing versus relying on lifts from family/friends. Non-drivers and less frequent drivers had poorer outcomes versus current drivers. These results highlight the importance of being able to travel independently whether by car or public transport. Opportunities to support this should be considered when planning future transport needs of ageing populations.
PUBLISHED
Keywords: Transportation, Social participation, Mental health, Loneliness, Aged; Ageing